Deciphering the mechanism of O2 reduction with electronically tunable non-heme iron enzyme model complexes. Issue 26 (12th June 2018) - Surendhran, Roshaan; D'Arpino, Alexander A.; Sciscent, Bao Y.; Cannella, Anthony F.; Friedman, Alan E.; MacMillan, Samantha N.; Gupta, Rupal; Lacy, David C.
Abstract : A homologous series of electronically tuned ligands were prepared and some of their corresponding Fe complexes were prepared and a Hammett plot of the rates of O2 reduction allowed us to infer important details of the mechanism. Abstract : A homologous series of electronically tuned 2, 2 ′, 2 ′′ -nitrilotris( N -arylacetamide) pre-ligands (H3 L R ) were prepared (R = NO2, CN, CF3, F, Cl, Br, Et, Me, H, OMe, NMe2 ) and some of their corresponding Fe and Zn species synthesized. The iron complexes react rapidly with O2, the final products of which are diferric mu-oxo bridged species. The crystal structure of the oxidized product obtained from DMA solutions contain a structural motif found in some diiron proteins. The mechanism of iron mediated O2 reduction was explored to the extent that allowed us to construct an empirically consistent rate law. A Hammett plot was constructed that enabled insightful information into the rate-determining step and hence allows for a differentiation between two kinetically equivalent O2 reduction mechanisms.